1992
DOI: 10.2134/agronj1992.00021962008400020008x
|View full text |Cite
|
Sign up to set email alerts
|

Soybean Seed Quality Response to Drought Stress and Pod Position

Abstract: The effects of drought stress on soybean (Glycine max (L.) Merr.] seed quality may be influenced by morphological plant characteristics and the timing of drought stress. Determinate soybean plants were grown near Ames, lA, to ascertain the influences of the timing and frequency of drought stress and pod position on seed quality (as mea· sured by germination, seedling dry weight, and seed leachate current). Plants were well-watered (high reproductive load) or drought-stressed at Dowering (R2) to decrease pot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
30
1
4

Year Published

1994
1994
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 51 publications
(38 citation statements)
references
References 17 publications
3
30
1
4
Order By: Relevance
“…Hommel-adjusted p-values were estimated (p < 0.0001) for the same varieties (Komsomolskoe 996 and Kazanskoe 176) (Table 4). However, our data were not consistent with other reports on soybean [20], pea [21], and corn [22], where water deficit decreased seed-filling duration. Across all three years, the five varieties with the quickest maturity in both irrigated and non-irrigated fields were Bolgar 159, Kamusinszkoe 67, TU-85-087-01, Turghai, and Tuvinskoe with 82, 83, 85, 86, and 86 days, respectively.…”
Section: Days To Heading and Maturitycontrasting
confidence: 99%
“…Hommel-adjusted p-values were estimated (p < 0.0001) for the same varieties (Komsomolskoe 996 and Kazanskoe 176) (Table 4). However, our data were not consistent with other reports on soybean [20], pea [21], and corn [22], where water deficit decreased seed-filling duration. Across all three years, the five varieties with the quickest maturity in both irrigated and non-irrigated fields were Bolgar 159, Kamusinszkoe 67, TU-85-087-01, Turghai, and Tuvinskoe with 82, 83, 85, 86, and 86 days, respectively.…”
Section: Days To Heading and Maturitycontrasting
confidence: 99%
“…II). Our data were consistent with other reports on soybean [22], pea [17] and corn [26], which showed that drought stress during seed filling had no effect on seed growth rate but decreased seed-filling duration and individual seed weight. Earliness in barley is an advantageous trait in conditions of terminal drought stress in Mediterranean environments [1,7,8,10].…”
Section: Grain Development and Filling Durationsupporting
confidence: 93%
“…The initial biomass values at emergence (Green and Sudia, 1969;Blum et al, 1980;Smiciklas et al, 1992;Richardson and Bacon, 1993;Pinhero and Fletcher, 1994;Hameed et al, 2003) were set considering the average planting density based on the plant and row spacing typical for each crop. Starting from the day of emergence, a daily LAI value was estimated based on leaf carbon (details follow), for deriving fPAR and estimating sub hourly photosynthetic assimilate, respiratory carbon (i.e.…”
Section: Detailed Schemementioning
confidence: 99%